2004
DOI: 10.1097/01.ico.0000126437.33375.6c
|View full text |Cite
|
Sign up to set email alerts
|

Mucous Membrane Pemphigoid in a Patient With Chronic Lymphocytic Leukemia

Abstract: Mucous membrane pemphigoid has been reported in association with a variety of nonhematologic malignancies. This case suggests that mucous membrane pemphigoid may also occur in B-cell CLL and supports the concept that autoantibodies play a role in the pathogenesis of this cicatricial conjunctival disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the literature there are numerous works reported that associate mucous membrane pemphigoid (MMP) with malignancies, including lung cancer [83], pancreatic adenocarcinoma [84], gastric adenocarcinoma [85], and squamous cell carcinoma of the conjunctiva [86] there are only two cases reported of MMP with oral manifestations associated to lymphoproliferative disorders: a B-cell lymphoma [87] and chronic lymphocytic leukemia [88]. It has been described in the literature that large amount of cases have connection between bullous pemphigoid (BP) and lymphoproliferative disorders such as chronic lymphocytic leukemia [8991] and lymphoblastic lymphoma [92].…”
Section: Classification and Related Aspects Of The Oral Pathologiementioning
confidence: 99%
“…In the literature there are numerous works reported that associate mucous membrane pemphigoid (MMP) with malignancies, including lung cancer [83], pancreatic adenocarcinoma [84], gastric adenocarcinoma [85], and squamous cell carcinoma of the conjunctiva [86] there are only two cases reported of MMP with oral manifestations associated to lymphoproliferative disorders: a B-cell lymphoma [87] and chronic lymphocytic leukemia [88]. It has been described in the literature that large amount of cases have connection between bullous pemphigoid (BP) and lymphoproliferative disorders such as chronic lymphocytic leukemia [8991] and lymphoblastic lymphoma [92].…”
Section: Classification and Related Aspects Of The Oral Pathologiementioning
confidence: 99%
“… Azathioprine and steroid-sparing therapy. N/A Iaccheri et al, 2004 1 39 M MMP Oral mucosa N/A N/A Bilateral Photophobia, thickened eyelid, conjunctival injection, foreshortening of fornices, symblephara, conjunctivitis, trichiasis, and keratopathy No N/A Topical antibiotic, amphotericin B drop, cyclophosphamide, subcutaneous cytosine arabinoside, IVIg therapy, and prednisone Seth et al, 2004 1 64 M MMP Palate, tongue, throat Blisters N/A Bilateral Conjunctival ulceration and symblepharon formation No Oral steroids on a tapering dose IV cyclophosphamide Lifshitz et al, 2004 1 20 M Pemphigus vulgaris Buccal mucosa, palate, pharynx, and larynx Erosions and blisters N/A Bilateral Conjunctival hyperemia, diffuse induration and thickening of eyelids, lid margin erosions in upper and lower lids No Oral prednisone, triamcinolone, and azathioprine Dexamethasone and chloramphenicol drops, antiglaucomatous drops, fusidic acid ointment, and artificial tears Canizares et al, 2006 5 52 F: 5 MMP Gingiva, hard palate, and tongue Erosion 48 months Bilateral Dry eye syndrome, symblephara, conjunctival and corneal ulceration, subepithelial erythema, fibrosis, keratopathy, and nuclear sclerosis No Dapsone, azathioprine sodium, clobetasol propionate ointment, nystatin, prednisone, etanercept, dexamethasone elixir, and topical fluocinonide gel IVIg, prednisone, dapsone, clobetasol propionate, nystatin, hydrochlorothiazide, cyclophosphamide, valacyclovir hydrochloride, acyclovir, cyclosporine, and mycophenolate mofetil Palleschi et al, 2007 3 53 M: 1 F: 2 Pemphigus vulgaris Palate Erosion 2 months, synchronous ...…”
Section: Resultsmentioning
confidence: 99%
“…Both chronic leukemia and lymphoma have been reported with DH [49][50][51] and PNP [52][53][54]. Based on few case reports, MMP [55][56][57] is not rare finding in leukemia. There has been only one case of BP reported in patient with leukemia [58].…”
Section: Malignancies Associated With Abdmentioning
confidence: 99%